Comparative Analysis of the GH/IGF-1 Axis during the First Sixth Months in Children with Low Birth Weight - Luciana Pessoa Maciel Diniz; Taisy Cinthia Ferro Cavalcante; Amanda Alves Marcelino da Silva (MDPI AG, 2023)
Objective: To analyze the relation between alterations in the growth hormone (GH)/insulin-like growth factor 1 (IGF-1) axis during the first 6 months of life and weight in children born in the lower-middle São Francisco region. Methods: This is an analytical cohort and exploratory. Thirty children, were formed two groups, one of low birth weight children (LBW, n = 15) and another of normal weight (NBW = 15) were initially identified in a hospital and reapproached at 3 and 6 months of age. Birth weight and alterations in GH/IGF-1 curves were measured at birth and the third and sixth months of life. Results: Weight gain during the 6 months of follow-up in newborns with a low birth weight was greater compared to newborns with a normal birth weight. All children who were born with a low birth weight had an altered GH/IGF-1 curve at birth (p = 0.002). Most newborns with a low birth weight maintained the alteration in the GH/IGF-1 curve at the third month of life (p = 0.027). Regarding the GH/IGF-1 curve at the sixth month, alteration persisted in greater proportion among children with a low birth weight. Conclusions: Alterations in insulin resistance markers, demonstrated by increased GH without a proportional increase in IGF-1, were observed to be significant in children with a low birth weight with greater adiposity in this group which may increase the risk of metabolic diseases in later life.